Pulmonary Vein Aneurysm Secondary to Mitral Regurgitation: Rare and Confusing Lesion - Erkanli, Korhan; Yazici, Pinar; Bakir, Ihsan (The Thoracic and Cardiovascular Surgeon, 2014)
A 54-year-old woman was referred to our institution suffering from severe dyspnea and asthenia due to progressive heart failure. Multidetector computed tomography angiography revealed biatrial enlargement with an image of pulmonary vein aneurysm. She underwent valvuloplasty for mitral and tricuspid valves, ligation of left atrial appendage, and left atrial reduction plasty concomitant with minimaze procedure using radiofrequency ablation but no intervention for aneurysm.
Keywords: mitral valve regurgitation; pulmonary vein aneurysm; ablation; computed tomography